Screening fungi For lipid production For consolidated bioprocessing - Hasni, Mohd Haffizi; Ahmad, Farah; Athoillah, Ahdyat Zain; Mansor, Mariatul Fadzillah (Kulliyyah of Engineering International Islamic University Malaysia (IIUM) 50728 Kuala Lumpur Malaysia, 2018)
This paper discusses about the production of lipid and glucose by three different fungi; Aspergillus niger, Aspergillus Oryzae, and Rhizopus sp.. Biodiesel consisting of methyl esters can be produced from fungal-based lipids through transesterification. Biodiesel can be produced from various carbon substrates. However, the existing production of biodiesel from lignocellulosic biomass is not economically feasible due to the multiple processes required; (1) pre-treatment process to break down complex structure of lignin-hemicellulose-cellulose matrix, (2) saccharification of cellulose via cellulases and xylanases into simple sugars, and (3) fermentation of simple sugars. Consolidated bioprocess (CBP) combines saccharification and fermentation into one reactor. A single microorganism needs to be able to produce cellulase, break down cellulose to produce simple sugars, and ferment it to produce lipid in CBP. The objective of this study is to find the most promising fungi amongst the studied strains to be used in CBP by investigating the fungi’s ability to produce lipid. M9 medium supplemented with carboxymethylcellulose was used for glucose production and was incubated for 6 days. Basic media was used for lipid production and Bligh and Dyer lipid extraction method was used to extract lipid from fungi. The results showed that Rhizopus sp. has the potential to be promising microorganisms for CBP as it has the highest lipid productivity and lowest standard deviation of glucose production in comparison to the other fungi. Although it did not produce the highest glucose concentration, this may be solved in subsequent experiment by media optimization.